Molecular Evolutionary Analyses of the RNA-Dependent RNA Polymerase (RdRp) Region and VP1 Gene in Sapovirus GI.1 and GI.2 - Fuminori Mizukoshi; Ryusuke Kimura; Tatsuya Shirai; Asumi Hirata-Saito; Eri Hiraishi; Kosuke Murakami; Yen Hai Doan; Hiroyuki Tsukagoshi; Nobuhiro Saruki; Takeshi Tsugawa; Kana Kidera; Yoshiyuki Suzuki; et al. (Microorganisms)
Human sapovirus (HuSaV) is a significant cause of gastroenteritis. This study aims to analyze the evolutionary dynamics of the RNA-dependent RNA polymerase (RdRp) and capsid (VP1) genes of the HuSaV GI.1 and GI.2 genotypes between 1976 and 2020. Using bioinformatics tools such as the Bayesian phylogenetics software BEAST 2 package (v.2.7.6), we constructed time-scale evolutionary trees based on the gene sequences. Most of the recent common ancestors (MRCAs) of the RdRp region and VP1 gene in the present HuSaV GI.1 diverged around 1930 and 1933, respectively. The trees of the HuSaV GI.1 RdRp region and VP1 gene were divided into two clusters. Further, the MRCAs of the RdRp region and VP1 gene in HuSaV GI.2 diverged in 1960 and 1943, respectively. The evolutionary rates were higher for VP1 gene in HuSaV GI.1 than that in HuSaV GI.2, furthermore, were higher in GI.1 Cluster B than GI.1 Cluster A. In addition, a steep increase was observed in the time-scaled genome population size of the HuSaV GI.1 Cluster B. These results indicate that the HuSaV GI.1 Cluster B may be evolving more actively than other genotypes. The conformational B-cell epitopes were predicted with a higher probability in RdRp for GI.1 and in VP1 for GI.2, respectively. These results suggest that the RdRp region and VP1 gene in HuSaV GI.1 and GI.2 evolved uniquely. These findings suggest unique evolutionary patterns in the RdRp region and VP1 gene of HuSaV GI.1 and GI.2, emphasizing the need for a ‘One Health’ approach to better understand and combat this pathogen.